IMPLEMENTASI ALGORITMA BLOWFISH PADA APLIKASI PENGAMANAN SURAT ELEKTRONIK (MAIL CLIENT) BERBASIS WEB - Megira, Selvy (Universitas Lembah Dempo, 2021)
Exchanging information is a common thing that almost everyone has done, one of the communication media that can be used is email. Because of the ease of accessing communication media by everyone, it has an impact on the security of information using these media. Then many people are trying to find ways how to secure information in exchanging information. one way is to combine email and cryptography applications that use a symmetric key algorithm, where the encryption and decryption keys are the same but if the decryption key is sent separately this allows the key to be known by eavesdroppers. In this final project, an email and cryptographic application is designed, in designing this application using the SDLC (Software Development Life Cycle) system development method with the waterfall model. The application uses the blowfish algorithm with the PHP programming language, where the encryption and decryption keys have been set by the system, this is done so that key information cannot be easily identified by eavesdroppers. The blowfish algorithm is a 64 bit block cipher algorithm where the blowfish key must be computed at the beginning, before the encryption and decryption process is carried out.